A chain mediation model on organizational support and turnover intention among healthcare workers in Guangdong province, China - Chen, Yuanyuan; Xia, Ping; Liu, Chaojie; Ye, Chumin; Zeng, Qi; Liang, Baofang (Frontiers in Public Health, 2024)
Introduction The outbreak of the Coronavirus Disease 2019 pandemic has presented significant difficulties for healthcare workers worldwide, resulting in a higher tendency to quit their jobs. This study aims to investigate the correlation between organizational support, work-family-self balance, job satisfaction, and turnover intention of healthcare professionals in China’s public hospitals. Methods A cross-sectional survey was conducted on 5,434 health workers recruited from 15 public hospitals in Foshan municipality in China’s Guangdong province. The survey was measured by organizational support, work-family-self balance, job satisfaction, and turnover intention using a five-point Likert scale. The association between organizational support, work-family-self balance, job satisfaction, and turnover intention was investigated using Pearson correlation analysis and mediation analysis through the PROCESS macro (Model 6). Results Organizational support indirectly affected turnover intention through three pathways: the mediating role of work-family-self balance, job satisfaction, and the chain mediating role of both work-family-self balance and job satisfaction. Conclusion Health administrators and relevant government sectors should provide sufficient organizational support, enhance work-family-self balance and job satisfaction among healthcare workers, and consequently reduce their turnover intentions.